GENERATION AND MATURATION OF HYDROCARBONS IN CEPU AREA, CENTRAL JAVA - B. Situmorang; Ludin Tambunan (Testing Center for Oil and Gas LEMIGAS, 1985)
Production from the Cepu area occurs from the Tuban and Kawengan Formations. Studies of organie richness and thermal maturity of thirty eight comventional core sanples from four wells penetrating the units by use of Rock-esal pyrolysis method reveal that a high total organic content (>0.30%) occurs in part of the Tuban Formation whereas a low total organie content (0.170.07%) is observed in the Kawengan Formation. Thermal maturity range is immature to maature with T-max ranging from 339Â°C to 435Â°C with the mature stage being confined to the Tuban Formation. The main kerogen type is structured kerogen (type III), with limited occurrence of unstructured kerogen (type II).Those results muggest that generution of gas occurred probably in the Tuban Fomation, vertically mi- grated and trapped at relatively shallow depths. It also implies that the more mature source-beds with marine kerogen could be found in the deeper sedimentaryÂ